2017
DOI: 10.1111/cge.13101
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐exome sequencing is a valuable diagnostic tool for inherited peripheral neuropathies: Outcomes from a cohort of 50 families

Abstract: The inherited peripheral neuropathies (IPNs) are characterized by marked clinical and genetic heterogeneity and include relatively frequent presentations such as Charcot-Marie-Tooth disease and hereditary motor neuropathy, as well as more rare conditions where peripheral neuropathy is associated with additional features. There are over 250 genes known to cause IPN-related disorders but it is estimated that in approximately 50% of affected individuals a molecular diagnosis is not achieved. In this study, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 42 publications
4
41
2
6
Order By: Relevance
“…The diagnostic yield of NMD panel in pediatric and adolescent cases (32.5%) was higher than in adult cases (24%). This is compatible with two previous HMN cohorts providing data on the age of onset (Hartley et al, 2017;Schabhuttl et al, 2014), and emphasizes the importance of HTS diagnostics for non-5q-SMA in childhood. An early diagnosis for those cases may improve decision-making for symptomatic interventions, especially for such conditions as SMA with lower extremity predominance (SMALED2) in which no severe progression of weakness is expected (Neveling et al, 2013;Peeters et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The diagnostic yield of NMD panel in pediatric and adolescent cases (32.5%) was higher than in adult cases (24%). This is compatible with two previous HMN cohorts providing data on the age of onset (Hartley et al, 2017;Schabhuttl et al, 2014), and emphasizes the importance of HTS diagnostics for non-5q-SMA in childhood. An early diagnosis for those cases may improve decision-making for symptomatic interventions, especially for such conditions as SMA with lower extremity predominance (SMALED2) in which no severe progression of weakness is expected (Neveling et al, 2013;Peeters et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…WES is used as an alternative approach in HTS‐based diagnostics for motor neuron disorders. Thus, in a cohort with inherited peripheral neuropathy, 102 out of 354 (29%) individuals were diagnosed by WES (Hartley et al., ). When we resequenced our unsolved cases by WES or WGS, the diagnostic contribution of WES/WGS was much lower for cases unsolved by NMD panel analysis (11%) than by LMND panel (53%), which most likely reflects the larger known disease genes included in the NMD panel (Figures B and A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients in this family had a relatively late age of onset and attacks were associated with a relatively minor drop in K + . Previously described bi‐allelic MCM3AP mutations, likely loss‐of‐function, have been reported to result in Charcot–Marie–Tooth neuropathy with distal weakness and mild intellectual disability . However, pleiotropy (mutations in 1 gene causing multiple different traits) is not uncommon as mutations in 1,274 genes have been reported to result in 2 or more phenotypes in the Online Mendelian Inheritance in Man database .…”
Section: Discussionmentioning
confidence: 99%
“…Over 1,000 mutations in more than 80 genes have been associated with IPN subtypes (Timmerman, Strickland, & Zuchner, ). However, despite these discoveries, numerous whole‐exome sequencing studies to screen IPN cohorts have shown 18%–50% of cases (or higher) remain unsolved creating a significant burden for IPN diagnosis (Drew et al., ; Hartley et al., ; Lupo et al., ; Schabhuttl et al., ). In these cases where exome sequencing has failed to identify mutations in specific genes, it is likely a proportion of the neuropathy cases may be due to noncoding DNA or structural variation (SV) mutations.…”
Section: Introductionmentioning
confidence: 99%